The Implementation of Islamic Religious Education in Forming Students’ Islamic Personalities at Junior High School Plus Darunna'im in the Era of Industry 5.0 - Verawati, Eka; Aziz Q, Ikhwan; Hayati, Rina Mida (International Journal on Advanced Science, Education, and Religion, 2025)
The emergence of Industry 4.0 and Society 5.0 has had a major impact on the world of education, including on the formation of student character. This research aims to find out why students are reluctant to follow the habits that have been implemented at school, such as dhuha prayers in congregation, reading the Koran before learning and other religious habits. Apart from that, this research also aims to identify the causes and impacts of ethics shown by students in their interactions with teachers and peers. The approach used is descriptive qualitative with data collection techniques through observation, interviews and documentation. This research involved PAI teachers and class IX students as the main respondents. The research results show that character education strategies are implemented through routine activities, role modeling and character cultivation. Routine activities are carried out through religious activities such as reading the Koran before learning and praying Dhuha together. The teacher's example plays an important role in forming students' attitudes of discipline and responsibility. Meanwhile, character cultivation helps students. This activity aims to make students aware of religious values, especially in training to be able to give alms. However, this research also found challenges in character education, especially in maintaining consistent student behavior outside of school and the minimal use of technology in character learning. The conclusion of this research confirms that the implementation of PAI in forming students' Islamic personalities in the industrial era 5.0 requires an innovative approach that integrates religious values with technology. Therefore, adaptive strategies are needed, including the use of digital media to support more effective and sustainable character learning